Pengembangan Kecerdasan Spiritual pada Mata Pelajaran Pendidikan Agama Is-lam dengan Konsep Modernisasi Pendidikan Menurut Fazlur Rahman - Alifani Izuddin Habiburrakhman (PATTINGALLOANG, 2021)
Dewasa ini anggapan berlebihan mengenai pentingnya IQ atau Intelligence Quotient marak di ke- hidupan masyarakat sekitar kita. Padahal sejatinya IQ tidak dapat berdiri sendiri, melainkan memer- lukan kecerdasan yang lain seperti EQ atau Emotional Quotient dan SQ atau Spiritual Quotient. Bahkan muara dari ketiga kecerdasan itu berakhir di dalam aspek spiritual atau Spiritual Quotient. Dampaknya, peserta didik akan memaknai pendidikan agama Islam sebagai mata pelajaran yang berhenti pada aspek ritual saja, tanpa memaknai dan menghayati nilai-nilai yang terkandung di da- lamnya. Mereka kemudian akan cenderung kaku, pasif dan stagnan serta jauh dari tujuan manusia sebagai khalifatullah dan insan kamil. Fazlur Rahman sebagai tokoh neo-modernis pemikiran Islam, memberikan solusi dengan gagasannya tentang kondisi pendidikan Islam yang ideal. Kondisi Pen- didikan yang ideal ini akan membantu pendidik dan peserta didik untuk mencapai kecerdasan spir- itual yang tinggi. Gagasan pendidikan Islam yang ideal dan akan mengangkat kecerdasan spiritual yang tinggi memiliki empat aspek yang perlu diperhatikan yakni Al-Qur’an, sistem pendidikan, pen- didik, dan peserta didik. Apabila keempat aspek tersebut dapat diperhatikan dan dilaksanakan dengan baik, maka akan tercipta generasi khalifah fil ‘ardl dan terbentuk manusia yang insan kamil. Kata Kunci : Kecerdasan Spiritual, Pendidikan Agama Islam, Fazlur Rahman, Pemikiran Islam Modern                                                  AbstractThe tremendous hype of the urgency of Intelligence Quotient (IQ) is spread widely nowadays. But, ideally Intelligence Quotient couldn’t standalone, but it needs another part such as Emotional Quotient (EQ) and Spiritual Quotient (SQ). Additionally, in the end Spiritual Quotient is a main part and essential part of this Quotient. The tremendous hype affects the student’s personality as they couldn’t understand the purpose of Islamic Education and its values. It stops on ritual aspect, as they couldn’t understand and feel how superbly calm Islamic studies values. They become numb, passive, stagnant, and also faraway from the purpose of human being as God’s representative as a leader on the earth and as a kind human. Fazlur Rahman as an Islamic neo-modernism figure gave some solutions with his thought about the ideal condition of Islamic Education should be. This ideal condition would help teacher and students to achieve and fulfill they potential throughout high Spiritual Quotient. The ideal concept proposed by Fazlur Rahman has four aspects that need special attention, there are Qur’an, education system, teacher, and student. If these aspects were well-prepared and well-implemented it would fulfill high quality human with good Spiritual Quotient aspect as well as they do their job as a God’s representative leader on the earth.